EFFECTIVENESS OF THE HOOK, BOOK, LOOK, AND TOOK (HBLT) TEACHING METHOD ON THE SPIRITUAL GROWTH OF EARLY CHILDHOOD STUDENTS AT PAUD RUMAH BELAJAR BABA - Priscila, Yossika; Nauli, Jhonnedy Kolang (PRODI PKAUD, IAKN TARUTUNG, 2024)
This study aims to evaluate the effectiveness of the Hook, Book, Look, And Took (HBLT) method on the spiritual growth of early childhood education (PAUD) students at Rumah Belajar Baba. The research employs a qualitative approach with a case study methodology, involving in-depth observation and document analysis. Data were collected through direct observation of learning activities, interactions between educators and students, and feedback from students and parents regarding the HBLT learning process. The results indicate that the HBLT method significantly contributes to the spiritual growth of students, as evidenced by an enhanced understanding of spiritual values, emotional engagement, and daily religious practices. The discussion reveals that the integration of technology in learning provides a more interactive and personalized experience, strengthening the connection between students and spiritual content. However, challenges in implementation, such as limitations in training, mentoring, and disparities in access, need to be addressed to improve the effectiveness of this method. The study recommends broader utilization of the Hook, Book, Look, And Took HBLT with adjustments to overcome existing obstacles and enhanced training for educators to maximize the potential of this method in the context of spiritual education.